Labor division and advantages and limits of participation in creation of intangible assets in industry 4.0: humans versus machines. Issue 4 (11th April 2020) - Lobova, Svetlana V.; Alekseev, Alexander N.; Litvinova, Tatiana N.; Sadovnikova, Natalia A.
Abstract : Purpose: The purpose of the work is to solve the set problem and to study the competition and perspectives of division of labor of humans and machines during creation of intangible assets in Industry 4.0. Design/methodology/approach: The research is performed with the help of regression and comparative analysis by building regression curves and with the help of the qualitative structural and logical analysis. Findings: The authors perform an overview of the factors that determine the advantages and limits of participation in creation of intangible assets in Industry 4.0, determine the perspectives and compile recommendations for division of human and machine labor during creation of intangible assets in Industry 4.0. Originality/value: The results of the performed research confirmed the general hypothesis that machine technologies allow improving the innovative, marketing and organizational and managerial activities and activities in the sphere of R&D through automatization of certain stages of the process of creation of intangible assets. The authors determine the factors that define the contribution of machine technologies in this process and their competitive advantages as compared to human intellectual capital during creation of intangible assets. These advantages prove the possibility and expedience of division of human and machine labor during creation of intangible assets.